Cloud Technologies Revolutionizing Global Education: A Technical Case Study - Mohammed Khaja Sirajuddin (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The article offers a thorough examination of how cloud technologies, by offering strong answers to persistent problems in the distribution of educational information, have radically changed the face of global education. Through the strategic application of cutting-edge technologies like serverless architectures, dynamic resource allocation systems, and content delivery networks, educational institutions have successfully developed accessible and scalable learning environments that cater to a wide range of international audiences. It painstakingly details how these technology deployments have produced notable advancements in several areas, such as improved system performance, cost-effective cost structures, and improved user experiences. The article describes how educational institutions have successfully integrated cloud infrastructure, emphasizing their capacity to effectively handle growing user demands while continuously preserving remarkable levels of system availability and performance metrics. Beyond the obvious operational advantages, the article offers a thorough roadmap for educational institutions looking to use cloud technology by identifying important factors for future deployments and delivering priceless insights into technical implementation tactics. It also highlights the transformational potential of cloud technology in contemporary education by highlighting how careful cloud adoption has improved the overall quality of educational delivery in addition to resolving technical issues. The article’s conclusions are especially important because they offer practical advice for educational establishments around the globe, showing how strategic technology adoption can both solve operational issues and further learning goals in a setting that is becoming more and more digital.